EFFECT OF GENETIC FACTOR ON REPRODUCTIVE TRAITS AND MORTALITY RATE IN PIGS - H.M. Yathish; Prem Prakash Choudhary; Sanjeev Ranjan; S. K. Misra; Jay Prakash Gupta (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Present study was undertaken to evaluate the effect of genetic factor on reproductive traits and mortality rate in four pig breeds namely Large Whiter Yorkshire (LWY), Landrace (LR), LWY x LR and LR x Desi (D) maintained at Regional Pig Breeding Station-cum-Bacon Factory, Haringhata, West Bengal. Data collected was subjected to Least Squares Analysis. The Least Squares Means ± SE of Litter Weight (kgs) at Birth was found to be 7.909±0.274, 9.638±0.179 , 9.794±0.240 and 8.113±0.271; and Litter Weight (kgs) at Weaning was found to be 36.039±2.005, 52.306±1.311, 53.582±1.757 and 37.075a±1.989, respectively, for LWY, LR, LWYxLR and LRxD pigs. Least Squares Means ± SE of Age at First Farrowing (Days) was found to be 369.444±2.891, 367.883±4.640, 347.913±3.492 and 356.554±3.203, respectively, for LWY, LR, LWYxLR and LR x D pigs. Least Squares Means ± SE of Mortality Rate (%) was found to be 31.593± 2.472, 20.636± 1.617, 19.332± 2.166 and 31.801± 2.446 for LWY, LR, LWYxLR and LR x D pigs, respectively. Also, The Least Squares Analysis has revealed a significant effect of genetic factor on litter weight at birth and at weaning, age at first farrowing and mortality rate. This result suggests the importance of genetic factor in improving reproductive efficiency of sows. Although this finding is of use in pig rearing practices, Least Squares Analysis of more data with environmental factors in addition to genetic factor will prove the importance of eliminating nongenetic factors in enhancing the returns on investments in pig husbandry.